Asesmen Autentik Setting Pembelajaran Berdiferensasi Dalam Pembelajaran Jarak Jauh Mewujudkan Merdeka Belajar SMP PGRI Mawah - kasliyanto, kasliyanto; Sampulawa, Sriyati; Darmawati, Siti; Zurimi, Safarin (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
The purpose of the research is for the development of authentic assessments of differentiated learning settings in distance learning to realize legitimate, reliable, objectiv and practical learning freedom. The Development Model of the assessment tool used in this study refers to the 4-D model consisting of defining, designing, developing, and deploying as discovered by Thiagarajan. The subjects in this study included 40 students of class VII of PGRI Mawah Junior High School. The trial was conducted using a pre-experimental design type one-shot case study. Data analysis techniques use qualitative descriptive. Instrument validation by experts and education practitioners using check list sheets with a likert scale of 1 (very lacking) – 4 (excellent). The test before the trial uses the validity formula of Gregory's contents, while the validity test after the trial (empirical validity) uses SPSS software with bivariate pearson analysis. Test the reliability, objectivity and practicality of the instrument using SPSS. Authentic assessment of differentiated learning settings in distance learning to realize independent learning both use guidelines and authentic assessment tools and instruments meet valid, reliable, objective and practical criteria for use because they have gone through revisions and trials.